3 (t – 3) = 5 (2t – 1) Solve The Equation

3 (t – 3) = 5 (2t – 1)

By removing brackets

=3t – 9 = 10t – 5

By transposing 9 to RHS and 10t to LHS we get

= 3t – 10t – 9 = 5

= -7t – 9 = 5

= – 7t = 14

= t =

\(\begin{array}{l} frac{14}{-7}\end{array} \)

= t = -2

Therefore, the equation is solved

Explore more such questions and answers at BYJU’S.

Was this answer helpful?

 
   

4.5 (11)

(35)
(11)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published.

*

*

close
close

DOWNLOAD

App Now

Ask
Question